Delfi AS v Estonia: The Liability of Secondary Internet Publishers for Violation of Reputational Rights under the European Convention on Human Rights. - Cox, Neville (Modern Law Review, 2014)
In October 2013, the European Court of Human Rights in Delfi AS v Estonia upheld a decision of the Estonian Supreme Court to impose liability on the owners of an internet news portal for defamatory comments which had been posted on their website by anonymous third parties. This note suggests that the decision is important in the context of publications with a 'public interest' element to them, because it appears to afford more protection to the right to reputation (deriving from the Article 8 right to privacy) and less to freedom of expression than was formerly the case. It is further argued that the Court's emphasis on the positive obligation of states to protect this right to reputation may mean that the existing English law in this area, including, potentially section 5 of the Defamation Act 2013, is inconsistent with the ECHR jurisprudence.